THE EFFECT OF LEARNING DISCIPLINE AND E-LEARNING PERCEPTIONS TOWARD ON LEARNING MOTIVATION WITH EMOTIONAL QUOTIENT AS A MODERATE VARIABLE - Eni Erwantiningsih (Yayasan Education and Social Center, 2022)
Learning during the Covid-19 Pandemic, which requires online methods without being able to meet face-to-face, impacts students, one of which is learning motivation. This impact can be seen from (1) not the maximum number of student attendance, (2) the tendency of students not to concentrate on learning from beginning to end, and (3) lack of understanding of the lecture material. This study aims to analyze the effect of learning Discipline and perceptions of e-learning learning on learning motivation with emotional quotient as a moderating variable. The research method used in this study is a causal associative method with a quantitative approach. Sampling was carried out using purposive sampling from students actively participating in lectures at the 5th and 7th semesters of the Faculty of Economics, Merdeka University, Pasuruan, as many as 122 people, all of which were used as research samples. The results of testing the hypothesis that the Learning Discipline variable (X1) has a positive and significant effect on learning motivation (Y) by obtaining the original sample value of 0.263 and P Values of 0.002 <0.05. E-Learning Learning Perception Variable (X 2 ) has a negative and insignificant effect on learning motivation (Y). V with the obtained original sample value of -0.125 and P Values of 0.059 > 0.05. The Emotional Quotient (Z) variable significantly moderated the discipline variable on learning motivation (Y) with P Values of 0.000 <0.05. The Emotional Quotient (Z) variable significantly moderated the E-Learning Learning Perception variable on learning motivation (Y) with P Values of 0.021 <0.05. The emotional quotient (EQ) significantly moderates learning Discipline and E-Learning Learning Perceptions of Learning Motivation. Based on the above analysis, it can conclude that Learning Discipline has a positive and significant effect on learning motivation and E-Learning Learning Perceptions have a negative and insignificant effect on Learning Motivation